2018
DOI: 10.1002/hpm.2526
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of motivation levels and associated factors among the nursing staff of tertiary‐level government hospitals

Abstract: The present study assessed the motivation level of nurses working in 3 highly decorated tertiary-level government hospitals of India and also underpins the factors attributing to motivation levels. A sequential mixed-method design was used in this study wherein 400 nurses working in 5 units of nursing care in the hospitals were enrolled based upon proportionate random stratified sampling techniques. A self-administered questionnaire with Likert scale was developed based upon scale used by Mbindyo et al. The at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Client safety and communication skills are issues that are constantly scrutinized in the training of health care professionals (Marks, ; Edwards, ; Archer, ). Training through simulation exercises offers pragmatic opportunities to build competence (Khalaila, ; Gillispie, ) and confidence (Barrett et al, ) in an interactive manner (Desy et al, ; Pandey et al, ) and within a risk‐free environment. The modalities that can be employed include, but are not limited to, screen‐based computer simulators (Abdel Meguid and Khalil, ; Havyer et al, ), standardized patients (Marks, ), complex task trainers (Rogers and Tutty, ; Christensen et al, ), and realistic patient simulators (Alcamo et al, ; Hill et al, ).…”
Section: Stimulating Intrinsic Motivation In Millennial Studentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Client safety and communication skills are issues that are constantly scrutinized in the training of health care professionals (Marks, ; Edwards, ; Archer, ). Training through simulation exercises offers pragmatic opportunities to build competence (Khalaila, ; Gillispie, ) and confidence (Barrett et al, ) in an interactive manner (Desy et al, ; Pandey et al, ) and within a risk‐free environment. The modalities that can be employed include, but are not limited to, screen‐based computer simulators (Abdel Meguid and Khalil, ; Havyer et al, ), standardized patients (Marks, ), complex task trainers (Rogers and Tutty, ; Christensen et al, ), and realistic patient simulators (Alcamo et al, ; Hill et al, ).…”
Section: Stimulating Intrinsic Motivation In Millennial Studentsmentioning
confidence: 99%
“…Educators have long recognized the importance of enhancing IM in students toward improving their educational experience (Everly et al, 1994;Deci and Ryan, 2012;Ramirez et al, 2018), since it has been demonstrated to be associated with deep learning (Sinclair et al, 2015) and improved academic performance (Desy et al, 2018). Reports have also indicated that students who were intrinsically motivated had higher self-esteem (Yilmaz et al, 2016), greater personal control of their lives (Pandey et al, 2018), and exhibited psychological well-being (Cook and Artino, 2016;Raza et al, 2018). It is universally acknowledged that the non-fulfillment of these needs is one of the major reasons for dropouts (Tai et al, 2016;Rothmaler et al, 2017;Mabel and Britton, 2018), or considerations of discontinuation of training among health care students (Jacobs et al, 2015;Brass et al, 2017).…”
Section: Theoretical Basis Of Intrinsic Motivationmentioning
confidence: 99%
See 3 more Smart Citations